Antisense Inhibition of Threonine Synthase Leads to High Methionine Content in Transgenic Potato Plants - Zeh, Michaela (American Society of Plant Physiologists, 2001)
Methionine (Met) and threonine (Thr) are members of the aspartate family of amino acids. In plants, their biosynthetic pathways diverge at the level of O-phosphohomo-serine (Ser). The enzymes cystathionine gamma-synthase and Thr synthase (TS) compete for the common substrate O-phosphohomo-Ser with the notable feature that plant TS is activated through S-adenosyl-Met, a metabolite derived from Met. To investigate the regulation of this branch point, we engineered TS antisense potato (Solanum tuberosum cv Désirée) plants using the constitutive cauliflower mosaic virus 35S promoter. In leaf tissues, these transgenics exhibit a reduction of TS activity down to 6% of wild-type levels. Thr levels are reduced to 45% wild-type controls, whereas Met levels increase up to 239-fold depending on the transgenic line and environmental conditions. Increased levels of homo-Ser and homo-cysteine indicate increased carbon allocation into the aspartate pathway. In contrast to findings in Arabidopsis, increased Met content has no detectable effect on mRNA or protein levels or on the enzymatic activity of cystathionine gamma-synthase in potato. Tubers of TS antisense potato plants contain a Met level increased by a factor of 30 and no reduction in Thr. These plants offer a major biotechnological advance toward the development of crop plants with improved nutritional quality.